Effectiveness of Kinesio Tape Administration on Ankle Sprain : Literature Review - Ardiansyah, Jepri; Sri Wahono, Alif; Nur Alfiah, Dini (International Journal of Social Research, 2024)
Ankle sprains are among the most common sports injuries, often resulting in pain, swelling, and functional limitations that can persist if not treated properly. This study aims to determine the effectiveness of Kinesio Taping (KT) in reducing pain and improving functional activity in patients with ankle sprains. A literature review method was employed, analyzing five selected studies published between 2013 and 2023, using databases such as PubMed and Google Scholar. The PICO framework guided the research, with inclusion criteria involving patients aged 10 to 30 years and exclusion criteria including systematic reviews and outdated articles. The results indicate that Kinesio Taping, applied at 25%-50% intensity for 20-30 minutes, three times a week over 4 weeks, significantly reduces pain and improves functional balance, as evidenced by tools like the Cumberland Ankle Instability Tool (CAIT) and Star Excursion Balance Test (SEBT). Compared to control interventions, KT consistently showed significant improvements (p<0.05) in pain reduction and joint stability. The findings confirm that Kinesio Taping is a non-invasive, cost-effective therapy that supports joint stability, improves lymphatic drainage, and accelerates recovery, making it a practical and evidence-based intervention for clinicians and athletes to promote faster recovery and reduce recurrence risk.